2020
DOI: 10.1155/2020/6530973
|View full text |Cite
|
Sign up to set email alerts
|

miR-425-5p Acts as a Molecular Marker and Promoted Proliferation, Migration by Targeting RNF11 in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common and dangerous malignant tumors in China, which causes a large number of deaths every year. MicroRNAs (miRNAs) dysfunction contributes to the malignant progression of tumors. The aim of our study was to investigate the relationship between the biological role of miR-425-5p and malignant progression of HCC. Our results showed that miR-425-5p expression was significantly upregulated in HCC tissues and closely related to the poor prognosis of HCC patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…It has been previously found that miR-425 regulated the proliferation, invasion and metastasis of hepatocellular carcinoma cells ( 36 ). These results are consistent with the previous findings that miR-425 can improve cell survival and is associated with a poor outcome ( 37 , 38 ). Overexpression of miR-425 promotes cell proliferation and migration via targeting RNF11 in HCC and it can also bind with FOXD3 to promote cell migration and invasion ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been previously found that miR-425 regulated the proliferation, invasion and metastasis of hepatocellular carcinoma cells ( 36 ). These results are consistent with the previous findings that miR-425 can improve cell survival and is associated with a poor outcome ( 37 , 38 ). Overexpression of miR-425 promotes cell proliferation and migration via targeting RNF11 in HCC and it can also bind with FOXD3 to promote cell migration and invasion ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the previous findings that miR-425 can improve cell survival and is associated with a poor outcome ( 37 , 38 ). Overexpression of miR-425 promotes cell proliferation and migration via targeting RNF11 in HCC and it can also bind with FOXD3 to promote cell migration and invasion ( 36 , 37 ). These results suggested that miR-425 is an oncogene to promote tumor progression.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that miR-362-3p/miR-425-5p exerts oncogenic effects by regulating HCC proliferation and migration. For example, miR-425-5p achieved its role in promoting the malignant progression of HCC by regulating RNF11 and was seen as a molecular target to predict the outcome of HCC patients [ 20 ]. Upregulation of miR-362-3p, which targets and regulates Tob2, thereby promoting the proliferation of hepatocellular carcinoma cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that silencing miR-425-5p inhibited the proliferation, migration, and invasion of OC cells, which was consistent with its role in other cancers. For example, miR-425-5p is significantly increased in hepatocellular carcinoma (HCC) tissues and is closely related to the poor prognosis of patients with HCC, which as an oncogene promotes the proliferation and migration of HCC cells via RNF11 or FOXD3 [ 18 , 19 ]. In colorectal cancer, miR-425-5p promotes cell proliferation, migration, invasion, and EMT by activating the CTNND1 -mediated β-catenin pathway [ 20 ].…”
Section: Discussionmentioning
confidence: 99%